2016
DOI: 10.1242/jcs.173674
|View full text |Cite
|
Sign up to set email alerts
|

KIF17 regulates RhoA-dependent actin remodeling at epithelial cell–cell adhesions

Abstract: The kinesin KIF17 localizes at microtubule plus-ends where it contributes to regulation of microtubule stabilization and epithelial polarization. We now show that KIF17 localizes at cell-cell adhesions and that KIF17 depletion inhibits accumulation of actin at the apical pole of cells grown in 3D organotypic cultures and alters the distribution of actin and E-cadherin in cells cultured in 2D on solid supports. Overexpression of full-length KIF17 constructs or truncation mutants containing the N-terminal motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 88 publications
0
16
0
Order By: Relevance
“…Further analysis indicated that regulators of actin assembly, such as RhoA, ROCK1, p-LIMK and p-cofilin, were downregulated in Kif17-KD oocytes. Kif17 regulates RhoA-dependent actin remodeling in epithelial cell-cell adhesions (Acharya et al, 2016). However, our co-immunoprecipitation results showed that components of the RhoA pathway bound to the tail domain of Kif17, suggesting that Kif17 forms a platform for these molecules.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Further analysis indicated that regulators of actin assembly, such as RhoA, ROCK1, p-LIMK and p-cofilin, were downregulated in Kif17-KD oocytes. Kif17 regulates RhoA-dependent actin remodeling in epithelial cell-cell adhesions (Acharya et al, 2016). However, our co-immunoprecipitation results showed that components of the RhoA pathway bound to the tail domain of Kif17, suggesting that Kif17 forms a platform for these molecules.…”
Section: Discussionmentioning
confidence: 64%
“…Septin 9 directly associates with the tail domain of Kif17 and modulates the interactions of this motor protein with membrane cargo (Bai et al, 2016;Wong-Riley and Besharse, 2012). Furthermore, Kif17 reportedly regulates RhoA-dependent actin remodeling at epithelial cell-cell adhesions (Acharya et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…51 In agreement, the KO of KAP3, a subunit of kinesin-2, results in decreased levels of N-cadherin and β-catenin in embryonic mouse neural precursors, 52 whereas the overexpression of another kinesin, KIF17, promotes the apical and junctional accumulation of actin and E-cadherin, respectively. 53 In epithelial Pkt2 cells cytoplasmic dynein transiently tethers MTs at sites of cell-cell contact during junction biogenesis, providing a track for the kinesin-dependent delivery of junctional components. 54 Another plus-end binding protein, CLIP170, targets MTs to AJs prior to apico-basal array assembly.…”
Section: Adherens Junctionsmentioning
confidence: 99%
“…KIF17 is a microtubule motor that interacts with the plus-end microtubule capture machinery at the cell cortex. Expression of KIF17 increases active RhoA and junctional actin levels, thereby stabilizing cellcell contacts (Acharya et al 2016). Although the GEF responsible for these effects is not known, these results suggest that modification of microtubule dynamics in more subtle ways also have an impact on RhoA signaling.…”
Section: Cytoskeletal Structures As a Platform For Signaling Complexesmentioning
confidence: 89%